Three elderly patients in which systemic edema developed with subsequent large amounts of exudate excretion from the whole body - Adachi, Kohzaburo; Yamade, Wataru; Fukushima, Hideki; Yoshitomi, Ryuji; Nishi, Shigeyuki; Ohtsuru, Noboru; Sugimoto, Tadahiko (Nihon Rōnen Igakkai zasshi, 2012)
Aim: Systemic edema is often observed at the terminal stages of cardiac or renal failure, with some cases showing a large amount of exudate excretion from the whole body. We investigated 3 such cases by comparison with those excreting less exudate. Methods: We examined the data of 3 male inpatients (age, 81, 89 and 97 years) with cardiac or renal failure who had systemic edema, with excretions of a large amount of exudate (more than 3,000 ml/day) and who subsequently died of malnutrition, oliguria or anuria. We used a control group (20 inpatients, 10 men and 10 women, mean age, 82) with excretions of less than 1,000 ml/day of exudate for comparison. Blood test values and the number of remaining days of life after the onset of oliguria/anuria were compared between the 2 groups. Moreover, the laboratory test findings of exudade and serum were compared within the subject group. Results: The subject group had a higher mean serum BUN level than the control group (138 mg/dl vs. 81 mg/dl). There were no significant differences in any other blood test values between the 2 groups. Remarkably, the number of remaining days of life after the onset of oliguria or anuria in the subject group was greater than that in the control group (mean, 14 days vs. 7 days). The laboratory data of the subject group showed that total protein, lipids, AST, ALT, γ-GTP, Ca and CRP levels were lower in the exudate than in the serum, whereas BUN, creatinine, UA, K and Cl levels showed no significant differences. Conclusions: It is suggested that a production of large amount of exudate is caused by a complex of various factors which increase vascular permeability. However, in the present study, BUN, UA and K levels in the exudate of patients were similar to those in the serum of the subject group. The longer survival observed after oliguria or anuria in the subject group may be explained by an increased excretion of K which occurs with a large amount of exudate. Further investigation is necessary for elucidation of the etiology of large amounts of exudate.